Balancing the interests of consumers & producers 11th Annual Asia Oil & Gas Conference, 11 - 13 June 2006, Kuala Lumpur Convention Centre, Kuala Lumpur, Malaysia - Asia Oil & Gas Conference 2006 : Kuala Lumpur); Petroleum Nasional Berhad; Malaysian Institute of Economic Research; Asian Strategy Leadership Institute; Conference Connection Inc. (Kuala Lumpur : Petronas, 2006)
Provides information such as tentative programme for that 3 days, participants, speakers, organizing committee, gallery, acknowledgement and announcement
Keywords: Petroleum industry and trade -- Asia -- Congresses; Gas industry -- Asia -- Congresses; Oil industries -- Asia -- Congresses; Power resources -- Asia -- Congresses